Pelvic Floor Distress Inventory – 20 As Quality of Life Score Predictor in Patient Using Pessary - Arwan, Berriandi; Andi Rinaldi; R.M. Sonny Sasotya; M. Rizkar Arev Sukarsa; Eppy Darmadi Achmad (Fakultas Kedokteran Universitas Andalas, 2025)
Introduction: Pelvic organ prolapse is one of women’s health major concern associated with decreased quality of life that may cause a disruption in the bladder, gastrointestinal and sexual dysfunction. Women’s Health Initiative (WHI) stated 41% of women aged 50-79 years pelvic organ prolapse symptoms and surgeries performed rate increased from 1.5 to 4.9 cases per 1,000 women per year. Objective: To determine changes in quality of life based on Indonesian version of Pelvic Floor Distress Inventory – 20 questionnaire in patients with pelvic organ prolapse. Methods: Prospective cohort study carried out in Hasan Sadikin Hospital, Bandung City, Indonesia during the period Januari 2022 – March 2023. The quality of life was followed up three months after hospital discharge. We used the Indonesian version of Pelvic Floor Distress Inventory – 20 (PFDI-20). Results: In this study, 20 subjects were involved. The result showed that significant reduction in the quality of life score in patients after the treatment of pelvic organ prolapse with conservative treatment such as pessary insertion based on scale Indonesia version of PFDI – 20 questionnaire, with the highest a preoperative PFDI-20 score of 275 and after therapy score reduction until 50. Conclusions: There is a reduction in quality of life scores in patients with pelvic organ prolapse underwent surgery. Further research should be conducted in large number to assess the quality of life of patients with pelvic floor dysfunction in Indonesia using these questionnaire.